Zawartość metali ciężkich w glebach na plantacji wierzby energetycznej nawożonej osadami ściekowymi = Content of heavy metals in soils fertilized with sewage sludge on "salix viminalis" cultivation - Kostecki, Jakub; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
We presented results of control on field with Salix viminalis which has been fertilized with sludge from sewage treatment plant in Sulechow. In article we showed changes of heavy metals contents in soils samples which has been collected in 2005, including seasons of the year. We also compared real conditions with forecasts.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); osady ściekowe; metale ciężkie; Salix viminalis; heavy metals; sewage sludge